2023
DOI: 10.1177/13524585231185247
|View full text |Cite
|
Sign up to set email alerts
|

Risk of COVID-19 in people with multiple sclerosis who are seronegative following vaccination

Safiya A Zaloum,
Callum H Wood,
Pooja Tank
et al.

Abstract: Background: People with multiple sclerosis (pwMS) treated with certain disease-modifying therapies (DMTs) have attenuated IgG response following COVID-19 vaccination; however, the clinical consequences remain unclear. Objective: To report COVID-19 rates in pwMS according to vaccine serology. Methods: PwMS with available (1) serology 2–12 weeks following COVID-19 vaccine 2 and/or vaccine 3 and (2) clinical data on COVID-19 infection/hospitalisation were included. Logistic regression was performed to examine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The minor increase in the number of pwMS who seroconvert under anti-CD20, and the greater proportion of those who do the same under ns-S1P, mirrors the vaccination response. Previous work is contradictory as to whether this correlates with a mitigated or sustained risk of infection [ 16 , 17 ]. Hospitalisation was not reported to be different between treatment groups after immunisation, and most importantly, none of the patients in our cohort had to undergo hospital care [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minor increase in the number of pwMS who seroconvert under anti-CD20, and the greater proportion of those who do the same under ns-S1P, mirrors the vaccination response. Previous work is contradictory as to whether this correlates with a mitigated or sustained risk of infection [ 16 , 17 ]. Hospitalisation was not reported to be different between treatment groups after immunisation, and most importantly, none of the patients in our cohort had to undergo hospital care [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed a greater risk of a breakthrough infection with lower anti-SARS-CoV-2-specific antibody levels and under certain disease-modifying therapies (DMTs) [ 13 , 14 , 15 , 16 ]. Especially under anti-CD20, the COVID-19 disease course was shown to remain more severe even after initial immunisation [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 However, immunocompromised individuals who have only a partial immune response to exogenous antigens are not fully immunoprotected after the relevant antigenic exposures. 3 Thus, multiple sclerosis (MS) patients whose humoral immunity has been depressed with therapeutic B‐cell depletion have a higher incidence of COVID‐19 infections 4 , 5 , 6 , 7 and COVID‐19‐related hospitalizations 8 after they have been vaccinated compared to non‐B‐cell‐depleted, vaccinated MS patients. 9 At the same time, B‐cell‐depleted patients do benefit from vaccinations, as evidenced by their many‐fold lower COVID‐19 hospitalization rates following vaccination relative to the pre‐vaccination epoch.…”
Section: Introductionmentioning
confidence: 99%